(untitled) (Homiletic, 2016)
The lives of black women in North America, historically, converge with socio-economic conditions, creating health disparities between black women and other demographic groups. These health disparities co-exist alongside narratives about black women that contribute to rendering the bodies, and subsequently the health, of black women invisible or nonessential. Many traditional approaches to preaching healing texts advocate for treating the human body as incidental to a greater aim of the text. In contrast, preaching with the lives of black women in view requires a hermeneutic that recovers the significance of the physical body, as it is grounded in theological frameworks that espouse communal belonging in conjunction with holistic existence. This essay explores the preaching of Baby Suggs, holy, from Toni Morrison’s Beloved, as a prototype for such a hermeneutic at work within preaching that makes way for healing and wholeness as real possibilities in contemporary contexts.